Bimetallic nanodots for tri-modal CT/MRI/PA imaging and hypoxia-resistant thermoradiotherapy in the NIR-II biological windows. (March 2020) - Lyu, Meng; Zhu, Daoming; Duo, Yanhong; Li, Yang; Quan, Hong
Abstract: Hypoxic tumor microenvironment leads to resistance or failure of radiotherapy (RT). As a non-invasive therapy, photothermal therapy (PTT) can improve the tumor hypoxic microenvironment in addition to directly killing tumor cells. PTT combined with RT (thermoradiotherapy) becomes an emerging treatment. Multi-functional nanoparticles used for hypoxia-resistant thermoradiotherapy in the second near-infrared (NIR-II) biological windows (1000–1700 nm) are urgently needed to be developed. Here, a facil method synthesis of ultra-small cysteamine (Cys)-coated FePd bimetallic nanodots (NDs) is reported. These NDs can not only produce effective hyperthermia (35.4%) when irradiated in the NIR-II region (1064 nm) but also have an enhanced radiation effect due to i) Hypoxic improvement in tumor tissues by photothermal treatment in the NIR-II Biological Windows can greatly enhance the sensitivity of tumor cells to radiotherapy ii) The ability of NDs to deposit radiation energy in tumors has further enhanced the sensitivity of tumor cells to radiotherapy. Meanwhile, NDs was a contrast agent for tri-modal imaging including computed tomography (CT)/magnetic resonance imaging (MRI)/photoacoustic imaging (PAI) in vitro and in vivo . Both in vitro and in vivo tests demonstrated good biocompatibility and excellent stability of NDs, indicating great potential for clinical applications.